Comparison of two devices for facial skin analysis. (25th October 2022) - Cook, Madison K.; Kaszycki, Margaret A.; Richardson, Irma; Taylor, Sarah L.; Feldman, Steven R.
Abstract: Background: The use of quantitative measures to assess patients' skin has turned the subjective nature of dermatology into an objective one. These measures allow for more accurate diagnosis and improved monitoring of diseases. While there are many skin analysis devices available, they often require specific equipment to function and can be costly, limiting their clinical use. Aims: The aim of our study was to compare a new skin analysis device that is easy to incorporate into dermatologic practice to a standard validated device. Methods: We recruited 50 patients from dermatology clinics and analyzed their skin with two facial analysis systems: an online application that can be downloaded on either an iPad or iPhone, and a computer‐based analysis system that utilizes a facial imaging photobooth. Scores were recorded and compared between the two devices for the following five skin characteristics; "spots, " "wrinkles, " "redness, " "texture, " and "pores." Results: The tablet and the computer analysis system had an agreement rate of 67.7%. The highest agreement was in assessing texture (72.0%) and pores (68.2%). The lowest agreeance was in assessing redness (64%) and wrinkles (67%). When assessing the relationship between patients' raw score for wrinkles and their age, there was a strong correlation with the tablet ( r = 0.79, p < 0.0001) compared with the computer system ( r = 0.26, p < 0.06). Conclusions: The application utilized in our study may serve as a cost‐effective and clinic friendly tool to assess patients' skin. It produces similar results to other skin analysis devices and may be more sensitive in detecting and quantifying wrinkles.